2008
DOI: 10.1007/s11055-008-9033-2
|View full text |Cite
|
Sign up to set email alerts
|

Localization of human cortical areas activated on perception of ordered and chaotic images

Abstract: The aims of this study were to identify the locations of areas in the human cortex responsible for describing fragmented test images of different degrees of ordering and to identify the areas taking decisions regarding stimuli of this type. The locations of higher visual functions were determined by functional magnetic resonance imaging (fMRI) using a scanner fitted with a superconducting magnet and a field strength of 1.5 T. The blood oxygen level-dependent (BOLD) method was based on measurements of the level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 9 publications
2
18
1
Order By: Relevance
“…Fokin et al, 2008;Takeichi et al, 2010). The current results show that BA7 is less activated, when stimuli are presented to the language dominant left (the RVF), compared to the on-dominant right hemisphere (the LFV).…”
Section: Discussionmentioning
confidence: 41%
“…Fokin et al, 2008;Takeichi et al, 2010). The current results show that BA7 is less activated, when stimuli are presented to the language dominant left (the RVF), compared to the on-dominant right hemisphere (the LFV).…”
Section: Discussionmentioning
confidence: 41%
“…Yet, opposed to medial frontal areas, the superior parietal cortex (BA7) has less frequently been reported to be involved in response inhibition 17, 32, 36, 37 . However, BA7 is involved in response inhibition whenever information is complex and probably difficult to categorize but essential for behavioral control 3133 . This is also likely the case in the current study, and especially so in the between-hands condition, because information from both hands need to be integrated.…”
Section: Discussionmentioning
confidence: 99%
“…These parietal regions have already been shown to be involved in response inhibition processes using somatosensory stimuli 11 . Moreover, they are involved during sensorimotor integration 29, 30 , also during response inhibition when sensory information is difficult to categorize but essential for behavioral control 3133 . This may be the case due to the effects of lateral inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…Both studies therefore support our notion of insulin-specific reduction in brain activity. Other regions affected by insulin include cortical frontal and temporal areas, which are involved in object recognition and decision making (29,33). The involvement of the hippocampus in food-specific processing is well established, and Pelchat et al (32) showed that this structure is especially involved in food craving.…”
Section: Discussionmentioning
confidence: 99%